Pengaruh Persepsi Harga, Lokasi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Toko AUS Lelateng Negara - Dewi, Gusti Ayu Putu Darti Paristya; Sudarsana, Komang; Negara, Made Dwipa (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This research aims to analyze the influence of price perception, location, and service quality on customer satisfaction at Toko AUS Lelateng Negara. The study employed a quantitative research design using a survey method. Data were collected by distributing questionnaires to customers who had purchased products at the store. The independent variables examined in this study were price perception, location, and service quality, while customer satisfaction served as the dependent variable. The collected data were analyzed using multiple linear regression analysis to determine both partial and simultaneous effects among variables. The findings indicate that price perception has a positive and significant effect on customer satisfaction, meaning that reasonable and affordable prices can increase customer satisfaction levels. In addition, location and service quality also positively and significantly influence customer satisfaction. Simultaneously, all variables significantly affect customer satisfaction. Therefore, businesses should maintain competitive pricing, strategic locations, and high-quality services to improve customer satisfaction and encourage customer loyalty in the long term.